Awareness of Silver Diamine Fluoride Among Dental Practitioners of Pakistan - Ashraf, Muneeba; Shamim, Laiba (Journal of the Pakistan Medical Association, 2023)
Dear Editor, I am writing this letter to bring attention to a concerning issue in Pakistan’s dental community: the lack of awareness about Silver Diamine Fluoride (SDF). Despite being discovered in 1960 by Professor Reiichi Yamaga from Osaka University Japan, many dentists in Pakistan are unfamiliar with this approach[1][2]. Silver Diamine Fluoride is a safe option to treat dentinal caries, particularly in primary teeth. Silver Diamine Fluoride has been widely used in other countries for many years and is effective in arresting dental caries and preventing their progression[3]. A meta-analysis and systemic review of 27 randomized controlled trials found that SDF was 60% more effective than other fluoride therapies in preventing caries[4]. According to the research, it is an effective option for children and elderly patients who may be unable to tolerate more invasive treatment options. Hence, it has reduced dental chair anxiety, making treatment easy for the patient and the practitioner[5]. Despite these benefits, SDF is not commonly used or discussed in Pakistan. A recent study conducted in Lahore found that only 25% of dental practitioners surveyed were aware of SDF, but only 10% had used it [6]. It is a concerning finding, particularly given Pakistan’s high prevalence of dental caries. Dental professionals in Pakistan must be made aware of the potential benefits of SDF and are encouraged to consider it as a treatment option for their patients. Doing so, can potentially reduce the need for more invasive and costly procedures and improve patient oral health outcomes. I urge the dental community in Pakistan to prioritize education and training on SDF and to consider its potential benefits for their patients.